Literature Review: Implementation Of PjBL In Instilling The Character Of Tolerance Of Elementary School Students In Social Studies Learning - Agustri, Intan Restu; Hidayat, Otib Satibi; Karsih, Karsih (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Instilling the character of tolerance in elementary school students has become an urgent necessityin addressing social, cultural, and student background diversity. One learning model consideredeffective in developing tolerance character is Project Based Learning (PjBL). This article aims toconceptually and empirically analyze the implementation of PjBL in fostering tolerance characteramong elementary school students through a literature study approach. The method used is asystematic literature review of various scientific sources derived from research findings, books, andrelevant academic journals published within the last ten years. The results of the review indicate thatPjBL promotes social interaction, cooperation, empathy, and respect for differences throughcollaborative project activities. The processes of discussion, joint problem-solving, and roledistribution within projects provide opportunities for students to learn to value others’ opinions.Based on the literature findings, the Project Based Learning (PjBL) model contributes not only tocognitive development but also to the formation of tolerance character in elementary school students.